Molecular basis for epithelial morphogenesis and ion transport in the Malpighian tubule. - Jonusaite, S.; Rodan, A.R. (Current opinion in insect science, 2021)
During development, the insect Malpighian tubule undergoes several programmed morphogenetic events that give rise to the tubule's ability to transport ions and water at unparalleled speed. Studies in Diptera, in particular, have greatly increased our understanding of the molecular pathways underlying embryonic tubule development. In this review, we discuss recent work that has revealed new insights into the molecular players required for the development and maintenance of structurally and functionally intact adult Malpighian tubules. We highlight the contribution of the smooth septate junction (sSJ) proteins to the morphogenesis and transport function of the epithelial cells of the Drosophila melanogaster Malpighian tubule and also discuss new findings on the role of the GATAe transcription factor. We also consider the roles of sSJ proteins in the fly midgut, as compared to the Malpighian tubule, and the importance of cellular context for the functions of these proteins.